LITERARY NEOREALISM OF ARTISTIC CREATIVITY BEGAN THE XX-th CENTURY - Reva-Lievshakova, L. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article deals with the issues of the formation, development and specificity of neo-realism of the beginning of the 20th century on the material of theoretical and critical works of the past and the present century. Attention is paid to the uniqueness of the relation of the philosophy of neo-realism with non-realistic manifestations in literary work. The position on the importance of neorealistic influence on the development of artistic creativity is expressed.